IMPLEMENTATION OF MESSAGE EMBEDDING INTO VIDEO USING RSA AND LSB2BIT ALGORITHMS - Abdillah, Ibnu Faiz; Hasugian, Abdul Halim; Armansyah, Armansyah (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
Protecting information during transmission is crucial to prevent unauthorized access. Steganography and cryptography are two commonly used methods for securing messages from illegal interception. Steganography involves two main components: a container and a secret message to conceal. This research focuses on embedding a message into an encrypted video. The embedding process utilizes the Least Significant Bit (LSB) algorithm, while encryption and decryption are performed using the RSA algorithm. In the LSB technique, the last two bits of the red component in each pixel are replaced with two bits from the encrypted message. Once replaced, the red value in each pixel is updated accordingly. Video steganography enhances message security by minimizing the likelihood of detecting hidden messages within the video. By combining the LSB method with RSA encryption, the confidentiality of the information is further strengthened.